IN VITRO RELEASE STUDIES OF CARBAMAZEPINE TABLETS AND BENZOYL METRONIDAZOLE SUSPENSIONS USING THE FLOW-THROUGH CELL APPARATUS AND SIMULATED GASTROINTESTINAL FLUIDS - Medina, Jose Raul; Hernandez, Jonathan; Hurtado, Marcela (International Journal of Applied Pharmaceutics, 2017)
Objective: To characterize the in vitro release of carbamazepine tablets and benzoyl metronidazole suspensions using the flow-through cell apparatus and simulated gastrointestinal fluids. Methods: TegretolÂ® tablets, FlagylÂ® suspension, and generic formulations of each were tested. Release studies were performed using an automated flow-through cell apparatus. Simulated gastric fluid (with and without pepsin) and simulated intestinal fluid (without pancreatin) at 16 ml/min and fasted state simulated intestinal fluid at 8 ml/min, all at 37.0Â±0.5 Â°C, were used as dissolution media. The quantity of dissolved carbamazepine and benzoyl metronidazole was determined at 5-min intervals until 60 min at 285 and 278 nm, respectively. Percentage dissolved at 60 min, mean dissolution time, dissolution efficiency values, and t10%, t25%, t50% and t63.2% were calculated. Mean values for all parameters were compared between the reference and generic formulations using StudentÊ¼s t-test. Dissolution data were fitted to different kinetic models. Results: Simulated gastric fluid without pepsin showed no discriminative capability for carbamazepine tablets. Significant differences were observed between the reference and generic formulations for almost all parameters (*P<0.05). In some cases, the logistic model best described the in vitro release of both drugs. Conclusion: Using an apparatus and media that best simulates the gastrointestinal environment, we identified differences in the rate and extent of dissolution of both drugs that could help to optimise the design of interchangeable formulations. Based on the physicochemical characteristics of carbamazepine and benzoyl metronidazole and the conditions in which the formulations were tested, these differences could be of clinical relevance. Â